Academician of NAMS of Ukraine, Rector of SE «DMA of Health Ministry of Ukraine» Georgy Viktorovych Dziak is 70 - SE DMA (Medičnì Perspektivi)
Academician of NAMS of Ukraine, Rector of SE «DMA of Health Ministry of Ukraine» Georgy Viktorovych Dziak is 70